Identification and Characterization of Approved Drugs and Drug-Like Compounds as Covalent Escherichia coli ClpP Inhibitors - Elisa Sassetti (International Journal of Molecular Sciences, 2019)
The serine protease Caseinolytic protease subunit P (ClpP) plays an important role for protein homeostasis in bacteria and contributes to various developmental processes, as well as virulence. Therefore, ClpP is considered as a potential drug target in Gram-positive and Gram-negative bacteria. In this study, we utilized a biochemical assay to screen several small molecule libraries of approved and investigational drugs for Escherichia coli ClpP inhibitors. The approved drugs bortezomib, cefmetazole, cisplatin, as well as the investigational drug cDPCP, and the protease inhibitor 3,4-dichloroisocoumarin (3,4-DIC) emerged as ClpP inhibitors with IC50 values ranging between 0.04 and 31 µM. Compound profiling of the inhibitors revealed cefmetazole and cisplatin not to inhibit the serine protease bovine α-chymotrypsin, and for cefmetazole no cytotoxicity against three human cell lines was detected. Surface plasmon resonance studies demonstrated all novel ClpP inhibitors to bind covalently to ClpP. Investigation of the potential binding mode for cefmetazole using molecular docking suggested a dual covalent binding to Ser97 and Thr168. While only the antibiotic cefmetazole demonstrated an intrinsic antibacterial effect, cDPCP clearly delayed the bacterial growth recovery time upon chemically induced nitric oxide stress in a ClpP-dependent manner.